Legal and Socio-Economic Challenges of E-Commerce in Uganda: Balancing Growth and Regulation - Aidonojie, Paul Atagamen; Okuonghae, Nosakhare; Najjuma, Aisha; Ikpotokin, Omobolanle Omolola; Obieshi, Eregbuonye (Faculty of Law Universitas Trunojoyo Madura, 2025)
Digital technology has reshaped various sectors of the world so that tasks are executed seamlessly within the shortest period through digital technology. It suffices to state that Uganda has also incorporated the same in enhancing virtually all sectors. For example, in recent times, buying, selling goods, and negotiating contracts are done majorly through digital technology. However, despite the prospect of e-commerce, some challenges may limit its viability in Uganda. In this regard, the study examines the legal and socio-economic issues concerning the adoption of digital commerce in Uganda. A hybrid method was used, and 304 questionnaires were distributed (through Google form) to respondents residing in Uganda. The data obtained were analysed using a descriptive and analytical approach. The study found that adopting e-commerce has greatly enhanced the commercial sector. However, despite the advantages of e-commerce, there are challenges, which include Data security and privacy, regulatory compliance, consumer protection from internet fraudsters and unfair trade practices, illiteracy of consumers, and poor and high cost of internet access. The study, therefore, concludes and recommends that e-commerce is a good innovation that could enhance and lead to further economic development in Uganda. In this regard, for smooth e-commerce operations in Uganda, there is a need for effective mechanisms in ensuring legal compliance and prosecution of anyone involved in data privacy breaches and internet fraudster. Furthermore, active and cost reduction of internet access could aid in enhancing the operation of e-commerce in Uganda. This research builds upon existing knowledge by discovering the legal and social-economic factors prohibiting the adoption of e-commerce in Uganda followed by specific recommendations and ensuring internet accessibility improvement in improving the country's digital economy.